Technology Beats Capital – Sharing the Carbon Price Burden in Federal Europe - Christina Roolfs; Beatriz Gaitan Soto; Ottmar Edenhofer; Kai Lessmann (ZBW - Leibniz Information Centre for Economics, 2021)
Passing federal environmental policy reform is a challenge as the approval of interest groups such as consumers and state-level governments is often a prerequisite. Among others, the burden sharing's progressivity has a large impact on reform approval. We investigate how carbon tax payments by states to a federal authority are influenced by differences in technological emission intensity and wealth and show how they can turn out to be at the expense of poor states. We show that a uniform federal carbon tax that is endorsed by all states with equal per capita transfers can theoretically put a higher burden on poorer states than richer states. The opposite applies for transfers based on historical emissions (sovereignty transfers) which reduce the burden of emissionintensive states. We test our results numerically in a general equilibrium model with a vertical federalism governance structure calibrated to the European Union. Our simulations show that a federal minimum emissions tax with sovereignty transfers is twice as high as for equal per capita transfers and also has a progressive effect.
Keywords: H77; H23; Q58; H87; H62; 330; Emission Regulation; Federalism; Unanimity; Transfers; Pareto-improvingpolicy; European Union